BEYOND EASE OF USE: TRUST AND SERVICE FEATURES AS KEY DRIVERS OF E-WALLET ADOPTION IN THE HALAL DIGITAL ECONOMY - Alif, Kharisma Nur; Tikawati, Tikawati; Rahmah, Fitria; Rivaldi, Muhammad Diki (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
The expansion of financial technology has accelerated the transition toward a cashless society in Indonesia, where digital wallets and QRIS have become increasingly popular among consumers. For Halal Micro, Small, and Medium Enterprises (MSMEs), adopting digital wallet services is not only a matter of efficiency but also of maintaining consumer trust and ensuring compliance with sharia principles. Despite its potential, adoption remains uneven, requiring further investigation into the key determinants that shape halal MSME owners’ decisions.This study aims to analyze the influence of ease of use, trust, and service features on the decision of halal MSME owners to provide digital wallet services. A quantitative approach was employed, with data collected from 60 halal MSME owners in Samarinda through purposive sampling. Structural Equation Modeling–Partial Least Squares (SEM-PLS) was applied to test the hypothesized relationships. A quantitative approach was employed using purposive sampling, involving 60 halal MSME owners in Samarinda. Data were collected through questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results reveal that perceived ease of use does not significantly affect decisions, whereas trust and service features have a significant positive influence. The study highlights a novel insight that, within the halal digital ecosystem, trust and superior service features outweigh ease of use as critical determinants of e-wallet adoption among MSMEs in emerging markets